Surgical removal of Coenurus cerebralis cysts located in the brain of sheep - Abuzer Tas; Ismail Sen; Fatih Hatipoglu; Hasan Huseyin Ari; Ali Risvanli; Ruslan Salykov; Nalan Ozdal; Mirbek Samsaliev; Sirgak Tolomusev; Nur Abdimanap Uulu; Aiperi Aitmyrza Kyzy (Journal of Applied Animal Research, 2024)
Coenurosis caused by Coenurus cerebralis poses a significant economic threat to sheep. To date, no effective treatment has been identified for this parasitic infection once it has settled in the brain. This study aimed to investigate the surgical removal of C. cerebralis cysts from the brains of infected sheep. Twenty sheep were utilized in the experiment, and the animals underwent a 24-hour fasting period before the surgical procedure. Various biochemical parameters, including TP, ALP, BUN, AST, CK, LDH, RBC, WBC, Hb, and Hct, were measured in the animals both before and one month after the operation. Anesthesia was induced by administering 2.2 mg/kg IV ketamine hydrochloride, five minutes after the administration of 0.1 mg/kg IV xylazine hydrochloride. Following anesthesia, the trepanation site was determined through percussion. Subsequently, an incision was made in the skin, exposing the skull bone. The skull was opened using a scalpel through trepanation, and the cysts were carefully removed. The results demonstrated that the presented surgical technique effectively treated C. cerebralis cysts in the sheep's brains, restoring normal motor and metabolic functions. Given these outcomes, it is concluded that the proposed surgical technique holds promise for practical application in the field.